Principles of ecotoxicology - Walker, C. H. (Colin Harold), 1936-; Sibly, R. M.; Hopkin, Stephen P.; Peakall, David B. (Boca Raton, FL : CRC Press, 2012)
"Now in its fourth edition, this exceptionally accessible text provides students with a multidisciplinary perspective and a grounding in the fundamental principles required for research in toxicology today. Its concisesness and readability makes it highly popular with students, while its focus on principles makes its the preferred choice of instructors.Discussing the fundamental chemical and ecological nature of pollution processes, the authors identifiy the major classes of pollutants and their environmental fate while examining those pollutants deserving closer scrutiny. They also cover naturally occurring poisons, the history of chemical warfare, population risk assessment, community structure, neonicotinoids, endocrine disruption, neurotoxicity, and the employment of biomarker strategies in field studies. In addition to updating the text throughout, this fourth edition--Includes a new chapter on future directions of ecotoxicologyProvides new material on nanoparticle pollution and effects of chemical weaponsOffers numerous new case studies, many from the U.S.Expands coverage of bioaccumulation, biomarkers, and risk assessment for affected populations "--
"Preface to Fourth Edition Since publication of the first edition of Principles of Ecotoxicology, both David Peakall and Steve Hopkin have died--serious losses to the international scientific community. Both made key contributions to the first two editions and this fourth edition is dedicated to their memories. The origins of this book lie in the MSc course titled "Ecotoxicology of Natural Populations," first taught at Reading in 1991. Ecotoxicology was then emerging as a distinct subject of interdisciplinary character. The structure of the course reflected this characteristic and was taught by people of widely differing backgrounds ranging from chemistry and biochemistry to population genetics and ecology. Combining the different disciplines in an integrated way was something of a challenge. The experience of teaching the course persuaded the authors of the need for a textbook that would deal with the basic principles of such a wide-ranging subject. The intention has been to approach ecotoxicology in a broad interdisciplinary way, cutting across traditional subject boundaries. However, the nature of the text is bound to reflect the experiences and interests of the authors"--
Rev. ed. of: Principles of ecotoxicology / C.H. Walker ... [et al.]. c2006.
Includes bibliographical references and index.
Keywords: Pollution -- Environmental aspects; Nature -- Effect of human beings on; Environmental toxicology; SCIENCE / Environmental Science; TECHNOLOGY & ENGINEERING / Environmental / General